Monocyte Tissue Factor Expression Induced by Plasmodium falciparum-Infected Erythrocytes - Pernod, Gilles; Polack, Benoît; Peyron, François; Luisy, Annick; Kolodié, Lucien; Ambroise-Thomas, Pierre; Santoro, Ferrucio (Thrombosis and Haemostasis, 1992)
Monocytes are active elements of the host response against Plasmodium falciparum. They are able to express tissue factor and trigger the extrinsic pathway of blood coagulation the activation of which remained unclear in malaria. Our aim was to assess the tissue factor expression of purified blood monocytes stimulated by cultured Plasmodium falciparum-infected erythrocytes. Malaria parasite induced an early generation of tissue factor with a peak between 8 and 12 h of stimulation. Maximum expression was observed for parasitemia ranging from 1 to 2%. Plasmodium falciparum culture supernatants had the same effect showing the existence of a soluble factor able to induce the tissue factor expression. These data, demonstrating an activation of the tissue factor pathway by the malaria parasite, emphasize thrombin generation. Therefore, thrombin could participate in malaria pathology either in the microcirculatory blockade via platelet and fibrinogen activation or as a mitotic.